2022
DOI: 10.3390/electronics11244143
|View full text |Cite
|
Sign up to set email alerts
|

A Transformer-Based DeepFake-Detection Method for Facial Organs

Abstract: Nowadays, deepfake detection on subtle-expression manipulation, facial-detail modification, and smeared images has become a research hotspot. Existing deepfake-detection methods on the whole face are coarse-grained, where the details are missing due to the negligible manipulated size of the image. To address the problems, we propose to build a transformer model for a deepfake-detection method by organ, to obtain the deepfake features. We reduce the detection weight of defaced or unclear organs to prioritize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…However, the early works were mainly focused on global features. Specifcally, we notice that forgery detection features are particularly evident in key facial organs such as the eyes, nose, and mouth [5,6,12]. For example, Xue et al [12] found that only using facial organs such as the nose, lips, eyes, eyebrows, and chin can detect deep forgery very well.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the early works were mainly focused on global features. Specifcally, we notice that forgery detection features are particularly evident in key facial organs such as the eyes, nose, and mouth [5,6,12]. For example, Xue et al [12] found that only using facial organs such as the nose, lips, eyes, eyebrows, and chin can detect deep forgery very well.…”
Section: Introductionmentioning
confidence: 81%
“…Wang et al [14] proposed a method that fused facial region feature descriptor for forgery determination by extracting feature points of a person's face. Xue et al [12] built a transformer model for a deepfake-detection method by organs to obtain the deepfake features. Yang et al [15] proposed a method for detecting diferences in face textures by amplifying the texture diferences between genuine and fake images and using a bootstrap flter to enhance postprocessing-induced texture artifacts and display the underlying features of the artifacts.…”
Section: Deep Forgery Discrimination Based On Image or Videomentioning
confidence: 99%
“…The work developed by (Xue et al, 2022) proposes a transformer-based deepfake detection method for facial organs, which can effectively differentiate deepfake media. The authors highlight that deepfake detection on subtle-expression manipulation, facial-detail modification, and smeared images has become a wide research hotspot.…”
Section: Cnn+grumentioning
confidence: 99%